Evaluate Nodes Importance in Directed Network Using Topological Potential - Teng Wang; Yanni Han; Jie Wu (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Mining concernful nodes in large network is a basic and important work in the research of complex network.There are some classic algorithms for ranking nodes in directed network. This paper provides a ranking algorithm based on topological structure.By defining and computing the topological potential score for each node,we can obtain a more accurate global ranking which can reflect nodes importance in the network.We also demonstrate the algorithm with using a real-world network.According to the experiment result,this method provides a general framework for some classic ranking measures. Furthermore,by optimizing influence factor,it can also reveal the position differences in network structure.